14C Analyses of Groundwater From the Botucatu Aquifer System in Brazil. Issue 3 (18th July 2016) - Aurelia, Annkarin; Silva, Kimmelmann E; da Cunha Rebouças, Aldo; Marlucia, Maria; Santiago, Freitas
Abstract : Measurements of 14 C activity as well as determinations of the stable isotope composition ( 18 O, 2 H and 13 C) of groundwater samples were made to investigate the flow path, origin, recharge and age of the Botucatu Aquifer System in Brazil, between 1984 and 1987. The stable oxygen isotope composition reflects infiltration during several climatic recharge conditions. Measured 14 C activities range from 0.4 to 94.2% modern. δ 13 C values enable us to distinguish two groundwater types of different origins. There is a gradual increase of 14 C ages from the outcrop area towards the central part of the basin, associated with a progression of the confining conditions. Anomalous fluoride contents seem to be correlated with high 14 C ages of the groundwater. The reliability of the 14 C data is discussed.